IMPLEMENTING CONSUMER PROTECTION LAW IN DIGITAL ECONOMY: LEGAL RESPONSIBILITIES OF E-COMMERCE DELIVERY SERVICE PROVIDERS - Dede Mulyati (PT. ZILLZELL MEDIA PRIMA, 2025)
The development of the business world in the current digital era has developed rapidly, Indonesian people prefer to use electronic media to meet all their wants and needs in everything such as fashion, household needs, etc. Such a situation makes digital platforms develop very rapidly with the aim of meeting the needs of the Indonesian people in meeting all needs in a practical and cost-effective way. Various platforms have emerged, including Buka Lapak as a digital platform that is growing rapidly today, for business development the platform opens partnerships in various regions so that the business reach is wider, one of which is in Cikeusik sub-district called Mitra Bukalapak Agen Tiga Putra. This research will identify the extent to which business actors, in this case Mitra Bukalapak Agen Tiga Putra, are responsible for the loss of goods sent by consumers and whether consumers receive adequate legal protection in accordance with the applicable provisions in Law Number 8 of 1999 concerning Consumer Protection. The Research Method uses a qualitative approach with an analytical descriptive method, where data is obtained through interviews, observations, and documentation conducted in the field. It is hoped that the results of this study can provide an understanding of the practice of legal responsibility in shipping services and consumer protection in the event of loss of goods.